Prevalence and severity of tinnitus in Polish otosclerosis patients qualified for stapes surgery - Dziendziel, Beata (Eur Arch Otorhinolaryngol, 2019)
PURPOSE: To assess the prevalence and severity of tinnitus among a group of Polish patients with otosclerosis who qualified for stapes surgery. A secondary objective was to gauge the relationship between tinnitus severity and hearing thresholds. METHODS: Based on the eligibility criteria, 460 adults with otosclerosis (236 women, 134 men) were included in the study. The Tinnitus Functional Index (TFI) was used to assess tinnitus severity. Hearing thresholds for air and bone conduction were established using clinical pure-tone audiometry in a soundproof cabin. RESULTS: Based on the medical interview, tinnitus was the first symptom of otosclerosis in 35% of the participants and 65% of all patients with otosclerosis experienced clinically significant, chronic tinnitus before stapes surgery. For 59% of patients, tinnitus was a significant or severe problem. The degree of hearing loss seemed to be marginally related to the severity of tinnitus reported by the patient. CONCLUSIONS: Tinnitus is a common complaint among patients with otosclerosis, being a significant or severe problem for more than half of them. For this reason, it is worth considering in the future the implementation of standardized questionnaires for the assessment of tinnitus severity as a routine procedure in the diagnostic process of patients with otosclerosis, as well as in the postoperative period, which will be the next stage of our study.